Around the world - Phelan, Matt (Candlewick Press, 2014)
Challenged with circling the world at the end of the nineteenth century, three very different adventurers--avid bicyclist Thomas Stevens, fearless reporter Nellie Bly, and retired sea captain Joshua Slocum--embark on epic journeys.